A galacturonan from Dioscorea opposita Thunb. regulates fecal and impairs IL-1 and IL-6 expression in diarrhea mice - Pan, Hao-Yu; Zhang, Chun-Qian; Zhang, Xiu-Qi; Zeng, Hui; Dong, Chun-hong; Chen, Xia; Ding, Kan (Glycoconjugate journal, 2022)
Antibiotic-associated diarrhea (AAD) is a common side-effect of antibiotic treatment resulting from an imbalance in the colonic bacteria. The hypothesis of this study is to ask whether polysaccharide from the rhizome of Dioscorea opposita which is recorded as conventional herbs and food for diarrhea treatment in Southeast Asia, may be an active compound against diarrhea induced by antibiotics. To address, firstly, a homogenous polysaccharide, DOP0.2-S-3 was characterized as a homogalacturonan containing linear repeating units of → 4)-α- D -GalA p (1 → 4)-α- D -GalA p (1 → with the average molecular weight of 14 kDa. DOP0.2-S-3 significantly reduced the water content and defecation times caused by AAD in mice, while it also remarkably attenuated the cytokines of IL-1β and IL-6 expression in mice colon tissues. DOP0.2-S-3 decreased potential pathogen and increased Bacteroidetes in the mice gut. These results suggested DOP0.2-S-3 might be a new leading compound for the functional foods or drug candidate development against AAD partially through regulating gut flora. Graphical abstract